1993
DOI: 10.3382/ps.0720535
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Addition of Cellular Metabolic Intermediates and Carcass Fat Deposition in Broilers

Abstract: Ninety-six 1-day-old male broilers were fed a diet containing 0, 2, 4, 6, 8, or 10% of a 1:1 mixture of pyruvic acid (PY) and dihydroxyacetone (DH) for ad libitum consumption for 42 days. Feed intake, body weight gain, and feed efficiency decreased linearly (P < .001) with increasing levels of PY and DH. There were no significant differences among treatments for abdominal fat percentage. Carcass chemical analysis revealed small but significant (P < .05) differences among dietary treatments for protein and fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
10
0
4
Order By: Relevance
“…In present trial, we also observed that the relative cloacal fat weight tended to increase in broilers fed with glycerol supplemented, especially at a level of 10% CG due to overestimation of metabolically energy assigned to glycerine [18] . Similarly, Lessard et al [6] have also found out that inclusion of 5% glycerol had increased the cloacal fat pad weight. However, the variances among treatments had no statistical meaning for this finding for present trial.…”
Section: Sehu Kucukersan Coskun Koksalmentioning
confidence: 97%
See 1 more Smart Citation
“…In present trial, we also observed that the relative cloacal fat weight tended to increase in broilers fed with glycerol supplemented, especially at a level of 10% CG due to overestimation of metabolically energy assigned to glycerine [18] . Similarly, Lessard et al [6] have also found out that inclusion of 5% glycerol had increased the cloacal fat pad weight. However, the variances among treatments had no statistical meaning for this finding for present trial.…”
Section: Sehu Kucukersan Coskun Koksalmentioning
confidence: 97%
“…Glycerine, also known as glycerol or glycerin, is a by-product of biodiesel production and usage of this product as an energy source for animal diets has been got attention in recent years [2][3][4] . Glycerine has been evaluated for poultry as a feed ingredient which provides energy for cellular metabolism [5][6][7][8][9] . Moreover, several studies have been performed for understanding effects of dietary glycerine addition on performance in broiler chickens [4,[7][8][9] , quails [10] , and laying hens [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported that glycerin is an acceptable feed ingredient for poultry (Campbell and Hill, 1962;Brambilla and Hill, 1966;Lin et al, 1976;Lessard et al, 1993;Simon et al, 1996Simon et al, , 1997Cerrate et al, 2006;Swiatkiewicz and Koreleski, 2009;Min et al, 2010). Adding glycerin up to 5% of the diet had no adverse effects on growth performance or carcass yield in broilers (Lessard et al, 1993;Simon et al, 1996;Cerrate et al, 2006).…”
Section: Crude Glycerin As a Feed Ingredient For Poultrymentioning
confidence: 99%
“…Adding glycerin up to 5% of the diet had no adverse effects on growth performance or carcass yield in broilers (Lessard et al, 1993;Simon et al, 1996;Cerrate et al, 2006). Increasing dietary glycerin above 10%, however, can adversely affect growth performance and meat yield of broiler chickens (Simon et al, 1996;Cerrate et al, 2006), although this may be due to reduced flowability of feed observed when 10% glycerin was supplemented (Cerrate et al, 2006).…”
Section: Crude Glycerin As a Feed Ingredient For Poultrymentioning
confidence: 99%
“…The influence of glycerine supplementation on weight gain, feed intake and feed conversion ratio was beneficial when included in the complete diet at levels from 5 to 10 %. Broilers fed a 20 % glycerine diet had the same weight, feed intake or feed conversion as control diet (Campbell and Hill, 1962;Lin et al, 1976;Lessard et al, 1993;Simon et al, 1996).…”
Section: Monogastricsmentioning
confidence: 99%